Organotypic co-cultures allow for immortalized human gingival keratinocytes to reconstitute a gingival epithelial phenotype in vitro - Roesch Ely, Mariana; Steinberg, Thorsten; Bosch, Franz X.; Wörtche, Eva; Whitaker, Noel; Wiest, Tina; Kohl, Annette; Komposch, Gerda; Tomakidi, Pascal (Differentiation, 2006)
We report here that the organotypic co-culture (OCC) system allows for significant preservation of the tissue-specific phenotype of human gingival keratinocytes (IHGK) immortalized with the E6/E7 gene of the human papillomavirus type 16 (HPV16). The approach adopted is based on the OCC system facilitating spatially separated cell growth and cell-to-cell interactions via diffusible growth factors.
Elektronische Reproduktion der Druck-Ausgabe
Available online 19 November 2009
In der Verfasserangabe ist der zweite Vorname von Franz Xaver Bosch falsch geschrieben
Gesehen am 19.02.2021